Fighting invisibility: indigenous citizens and history education in El Salvador and Guatemala. Issue 1 (2nd January 2019) - Gellman, Mneesha; Bellino, Michelle
ABSTRACT: El Salvador and Guatemala underwent civil wars that severely impacted both countries' most marginalized citizens, including indigenous peoples. Today, teaching and learning the violent past remain challenged in each country, with implications for indigenous and non-indigenous citizens alike. This article examines the impact of democratization in El Salvador and Guatemala in the educational sphere, documenting narrative trends on the topic of the civil wars and indigeneity in formal and informal education settings. We argue that distinct democratization and transitional justice processes have created opportunities and challenges for teaching and learning about indigenous peoples' roles and experiences in the civil wars in each country. Methodologically, the article draws on analyses of educational policy and formal curriculum in both contexts, supplemented by ethnographic data. We situate the study within democratization, transitional justice, and education literatures to document how teaching and learning the violent past is a highly politicized act with long-term implications for democratic quality in each country.